Microwave-assisted synthesis of superabsorbent agar-based magnetic composite hydrogel for drug delivery and anti-inflammatory studies - Muffarih Shah; Nasrullah Shah; Ismail Shah; Ibrahim Shah; Touseef Rehan; Khayala Mammadova; Abbas Khan; Noor Majeed; Maria Anjum; Mahmoud Elodemi; Afnan Jan; Ajmal Khan; et al. (Results in Engineering)
This study presents the synthesis of novel super absorbent ager base magnetic composite hydrogel (AMHs) through a microwave assisted polymerization technique. The composite hydrogels (control, MT, MS, and MN) were synthesized from 2-acrylamine-2-methylpropane sulfonic acid (AMPS), acrylic acid (AA), acrylamide (AM), and iron oxide magnetic nanoparticles (MNPs). Microwave assisted free radical polymerization was employed, using potassium persulfate is the initiator and N,N’ methylenebisacrylamide (MBA) as the cross linker under a nitrogen atmosphere to mitigate interference from oxygen. The structural, morphological and chemical characteristic of the synthesized hydrogels were thoroughly analyzed using Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), scanning electronic microscope (SEM), thermogravimetric analysis (TGA) and point of zero charger (PZC) measurements. The synthesized AMHs exhibited remarkable swelling capacities, with value of 19,840 %, 18,340 %, 14,850 % and 11,720 % for control, MT, MS and MN respectively. Drug adsorption studies specifically for ciprofloxacin, revealed a maximum adsorption capacity of 120.338 for MN, 114.038 mg/g for MS and 120.338 mg/g for MT and 102.138 mg/g for control, varying pH conditions and concentrations. Adsorption kinetics studies followed by Langmuir isotherm model and pseudo-second-order kinetics indicating a chemisorption mechanism. Drug release experiment show approximately 80 % of the loaded drug was released within 24 h. The MN sample showed minimal skin irritation and promising anti-inflammatory activity. The irritation test revealed no irritation (score 0) for C: IV 0.3 and C: 0.9 (II), with mild irritation (score 1) for others. Anti-inflammatory testing showed C: 0.6 (V) had the highest inhibition (46.66 %) at 0.5 g/kg, followed by C: 0.9 (II) (46.48 %) and C: 0.6 (I) (46.32 %). These results suggest AMHs are promising for drug delivery and wound healing.